Kepercayaan Masyarakat Terhadap Animisme Dan Dinamisme Didesa Dukun Gresik - zidni, moh (ISLAMIKA, 2024)
In a socio-cultural context, there are two concepts still believed by some communities, namely animism and dynamism. These beliefs shape the community's perception of spirituality related to forces, and thus, are known as ancestral beliefs. Both beliefs play a crucial role in forming social norms, customs, and religious practices in traditional societies. Animism and dynamism are also integral to how communities understand the relationship between humans, nature, and the surrounding spiritual world. Animism emphasizes belief in the existence of spirits in everything, whether living or non-living. Meanwhile, dynamism believes in the presence of supernatural powers inherent in certain objects. This paper will explore these two concepts in depth, their differences and similarities, and their impact on social and cultural life. It analyzes how these beliefs influence social practices, religious rituals, and the value systems of the X community. The study will also discuss efforts to adapt animistic and dynamistic beliefs in the face of modernization. Despite the widespread dissemination of major religions, remnants of animism and dynamism can still be found in various forms within modern culture. This analysis aims to understand how these ancient beliefs continue to persist and evolve over time.